Role of mPFC and nucleus accumbens circuitry in modulation of a nicotine plus alcohol compound drug state - Randall, Patrick A. (Addict Biol, 2019)
Combined use of nicotine and alcohol constitute a significant public health risk. An important aspect of drug use and dependence are the various cues, both external (contextual) and internal (interoceptive) that influence drug seeking/ taking behavior. The present experiments employed the use of Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) and complementary Pavlovian drug discrimination procedures (Feature Positive and Feature Negative training conditions) in order to examine whether medial prefrontal cortex (prelimbic; mPFC-PL) projections to the nucleus accumbens core (AcbC) modulate sensitivity to a nicotine+alcohol (N+A) interoceptive cue. First, we show neuronal activation in mPFC-PL and AcbC following treatment with N+A. Next, we demonstrate that chemogenetic silencing of projections from mPFC-PL to nucleus accumbens core decrease sensitivity to the N+A interoceptive cue, while enhancing sensitivity to the individual components, suggesting an important role for this specific projection. Furthermore, we demonstrate that clozapine-N-oxide (CNO), the ligand used to activate the DREADDs, had no effect in parallel mCherry Controls. These findings contribute important information regarding our understanding of the cortical-striatal circuitry that regulates sensitivity to the interoceptive effects of a compound N+A cue.